2013
DOI: 10.1016/s0924-9338(13)75780-8
|View full text |Cite
|
Sign up to set email alerts
|

451 – Study of relationship between domestic violence and health services utilization in married women in tehran, 2011–12

Abstract: Background review:Domestic violence against women (DV) in one of health problems that have 9–15% of burden of diseases in middle aged women and would lead to another health problems such as psychiatric disorders and could increase health services utilization and costs.Aim:To estimate prevalence of DV in married women in Tehran and its relation to health services utilization.Methods:A household survey of 615 married women in 22 city districts of Tehran in 2011 with a cluster sampling method was done. Demographi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Studies consistently report anxiety as a psychological health consequence among women who have experienced IPV (Ahmadzad-Asl, Davoudi, Zarei, Mohammad-Sadeghi, & Rasoulian, 2016;Dillon et al, 2013;Helfrich et al, 2008). In a study examining the correlation between IPV, depression, and anxiety among married women, Ahmadzad-Asl et al (2016) found that women who experienced physical abuse within the last 12 months reported having more clinically significant anxiety (47.8%) compared to women without any exposure to violence (29.3%). Helfrich et al (2008) found that 77% of women in a domestic violence shelter experience anxiety compared to a national average of 6.1%.…”
Section: Anxietymentioning
confidence: 99%
“…Studies consistently report anxiety as a psychological health consequence among women who have experienced IPV (Ahmadzad-Asl, Davoudi, Zarei, Mohammad-Sadeghi, & Rasoulian, 2016;Dillon et al, 2013;Helfrich et al, 2008). In a study examining the correlation between IPV, depression, and anxiety among married women, Ahmadzad-Asl et al (2016) found that women who experienced physical abuse within the last 12 months reported having more clinically significant anxiety (47.8%) compared to women without any exposure to violence (29.3%). Helfrich et al (2008) found that 77% of women in a domestic violence shelter experience anxiety compared to a national average of 6.1%.…”
Section: Anxietymentioning
confidence: 99%